Review of the Mechanisms for Preventing, Diagnosing, and Treatment of Pipe Sticking in Drilling Operations - Issa, Muntadher Adil; A. Alrazzaq , Ayad A. Alhaleem; Mukhtar, Yasir (Iraqi Journal of Chemical and Petroleum Engineering, 2023)
Stuck pipe is a prevalent and costly issue in drilling operations, with the potential to cost the petroleum industry billions of dollars annually. To reduce the likelihood of this issue, efforts have been made to identify the causes of stuck pipes. The main mechanisms that cause stuck pipes include drill cutting of the formation, inappropriate hole-cleaning, wellbore instability, and differential sticking forces, particularly in highly deviated wellbores. The significant consequences of a stuck pipe include an increase in well costs and Non-Productive Time (NPT), and in the worst-case scenario, the loss of a wellbore section and down-hole equipment, or the need to sidetrack, plug, or abandon the well. This paper provides a comprehensive review of the challenges associated with pipe sticking during drilling operations. The mechanisms of pipe sticking, analysis of differential sticking factors, guiding principles to minimize differential sticking, diagnosis approaches, and different treatment methods are discussed. This paper can serve as a guide for any problem involving stuck pipes in the petroleum industry.